2015
DOI: 10.1371/journal.pone.0128246
|View full text |Cite
|
Sign up to set email alerts
|

Early Depression Screening Is Feasible in Hospitalized Stroke Patients

Abstract: Background and PurposePost-stroke depression (PSD) is common but is not routinely assessed for in hospitalized patients. As a Comprehensive Stroke Center, we screen all stroke inpatients for depression, though the feasibility of early screening has not been established. We assessed the hypothesis that early depression screening in stroke patients is feasible. We also explored patient level factors associated with being screened for PSD and the presence of early PSD.MethodsThe medical records of all patients ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 20 publications
4
18
1
1
Order By: Relevance
“…Contrary to our results, it was reported that patients under 50 years old occupy a higher percentage of subjects with depression [23]. Also, it was recognized that younger patients appear to be more attentive about the prognosis of the disease [4,25].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our results, it was reported that patients under 50 years old occupy a higher percentage of subjects with depression [23]. Also, it was recognized that younger patients appear to be more attentive about the prognosis of the disease [4,25].…”
Section: Discussioncontrasting
confidence: 99%
“…Its prevalence was evaluated to be from 20 to 65%, contingent upon the population studied, the assessment tools, and the defining criteria of depression [3]. Post-stroke depression (PSD) is associated with more physical disability, particularly in day by day activities, poor functional outcome, and high death rate [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was observed that patients <50 years of age occupy a larger proportion of patients with depression. In the authors' clinical work, it was identified that younger patients appear to be more concerned about the prognosis of the disease (33,34). The factors that have an important role in the psychological state of younger patients requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…One of the providers who responded to the survey contemplated the possibility of “false positive screens” among hospitalized patients due to physical symptoms. However, previous studies (Karamchandani et al, ; Wagner et al, ) supported the feasibility and acceptability of depression screening in hospitalized patients using different screening tools, including the PHQ‐9, the screening tool used in this study (Kroenke et al, ).…”
Section: Discussionmentioning
confidence: 52%